Intestinal Absorption of Bile Salts - Karen Madsen (Canadian Journal of Gastroenterology)
Bile acids are secreted from the liver into the duodenum where they aid in the digestion and absorption of dietary lipids. Absorption of bile acids occurs through both ionic and nonionic diffusion in the jejunum and colon and through an active sodium ion-dependent carrier mechanism in the ileum. The prima, y bile acids synthesized in the liver can be converted by intestinal bacteria into secondary and tertiary bile acids. Bile acids may also be conjugated with glycine or taurine which results in an increase in the hydrophilicity and solubility of these compounds at physiological pH. The amount of passive diffusion of bile acids that occurs across the brush border membrane along the length of the entire intestine depends upon the ratio of ionized to nonionized bile acids coupled with the bile salt concentration and the individual permeability coefficients of monomers. Active transport of both conjugated and nonconjugated species of bile acids depends upon the presence of a single negative charge on the side chain. Maximal transport rates for bile acids are related to the number of hydroxyl groups present while the Michaelis-Menten constant for transport is dependent upon whether or not the bile acid is conjugated. Although active uptake of bile acids from the ileum has been considered the major route for bile salt absorption in the small intestine, the mechanism may actually be responsible for only a small proportion of the total bile acid pool absorbed from the lumen.